Mycotoxin Contamination of Edible Non-Timber Forest Products in Cameroon - Djeugap, Joseph Fovo (Toxins (Basel), 2019)
The prevalence and concentrations of three major mycotoxins, total aflatoxin (AFs), fumonisin (F), and zearalenone (ZEN), were determined on seven edible non-timber forest products (ENTFP) in Cameroon. A total of 210 samples consiting of 30 samples from each ENTFP commodity was collected from farmers and local markets in three agroecological zones of Cameroon and analyzed for moisture content and mycotoxins. Mycotoxins were analyzed using commercial enzyme-linked immunosorbent assay (ELISA) kits and results were validated using the VICAM fluorometric method. The European Union regulation of mycotoxins for human consumption (N°1881/2006) was adopted as reference. The moisture content of samples varied from 5.0% to 22.6%. Aflatoxin contamination was detected in 84.3% samples and only 5.7% exceeded the legal limit (10 ppb). Similarly, 53% of samples were contaminated with fumonisin and 5% of samples exceeded the legal limit (1000 ppb). Zearalenone contamination was detected in 92% of samples and 21% of samples exceeded the legal limit (100 ppb). This is the first report on mycotoxin contamination of ENTFP in the Congo Basin forest. The findings of this study will form a basis for educating farmers and other stakeholders of ENTFP values chain on mycotoxins and mycotoxin mitigation measures to produce safe ENTFP for local and international markets.